The burden of cirrhosis and other chronic liver diseases due to hepatitis B in children and adolescents: results from global burden of disease study 2019 - Chenyang Huang; Chenyang Huang; Yaxin Wu; Chao Zhang; Dong Ji; Dong Ji; Fu-Sheng Wang; Fu-Sheng Wang (Frontiers in Public Health, 2023)
BackgroundThe global burden of cirrhosis and other chronic liver diseases due to hepatitis B (collectively referred to as hepatitis B-associated cirrhosis in this paper) in children and adolescents must be understood and investigated.MethodsData were extracted from the GBD database, and calculations were performed at global, regional, and national level. We calculate the incidence, prevalence, and disability-adjusted life years (DALYs) and annual average percentage changes (AAPCs).FindingsGlobally, the prevalent cases of children and adolescents with hepatitis B-associated cirrhosis decreased from 125,053.98 × 10^3 in 1990 to 46,400.33 × 10^3 in 2019. Compared with 1990, the incidence rate of cirrhosis increased in low (95.51%) and low-middle SDI areas (26.47%), whereas it decreased in other SDI areas. The AAPC of incidence has increased in low-middle SDI areas (AAPC 0.12 [95% CI: 0.04–0.20]). At the regional level, the East Asia region has experienced the largest reduction. Conversely, Western Sub-Saharan Africa was the most serious region. Notably, South Asia was the only region where the AAPC of cirrhosis incidence (AAPC 0.77 [95% CI, 0.68–0.86]) increased.ConclusionGlobally, the overall burden of hepatitis B-associated cirrhosis in children and adolescents has declined significantly, but the number of cirrhosis incidence cases in low-middle and low-SDI areas has increased. The incidence in South Asia is rising, and the burden on Africa remains serious. Prevention and treatment of hepatitis B-associated cirrhosis in children and adolescents should not be ignored.